Market Warnings : Learning from the Short-Term Impact of COVID-19 on Stock Market Constituents - Sharma, Chandan; Singh, Archana; Yadav, Rajan (Indian Journal of Finance, 2023)
Purpose : The paper investigated the short-term impact of the lockdown announcement due to COVID-19 on various industries in India using firms’ stock returns and credit ratings. Design/Methodology : The paper used event study methodology to analyze abnormal returns on stocks and credit rating changes of firms following the lockdown to understand the impact on the debt servicing of firms. Findings : The paper found a heterogeneous impact of lockdown on various industries. Pharmaceuticals, chemicals, FMCGs, and telecom sectors saw positive abnormal returns, while textiles, financial services, construction, services, cement, and automobile sectors were the worst affected. The paper also found that smaller companies were more susceptible to the effects of such lockdowns. Indian subsidiaries of foreign MNCs and Central Government-owned firms fared better than privately-owned domestic firms. The debt servicing ability of firms was unimpacted due to the debt relief package announced to mitigate the impact of the lockdown. Practical Implications : The paper's findings have implications for investors and managers who can make informed decisions in advance to reduce the risk to their investment if such a black swan event is expected. The paper's findings could help policymakers identify sectors that require immediate support due to the disruption from such an event. Originality : The paper is unique in investigating the impact of the lockdown due to COVID-19 on companies across different industries, with different ownership groups and sizes. We have not come across such a detailed study investigating the impact of COVID-19 on various industries in India.